#TITLE_ALTERNATIVE# - KRISNAHADI (NIM 10202034) pembimbing : Dr. Gunawan Handayani, ARIF
The analysis of the seismic propagation velocity and the identification of discontinuities by means of reflections and refractions are the tools of classical seismic surveying. With surface waves methods the analyzed phenomenon is the geometrical dispersion of Rayleigh waves in heterogeneous media. The principle is that different frequencies produce particle motion and deformation that are significant and not negligible within a limited depth depending on the wavelength, and so the propagation of the different frequencies occurs down to different depths below the surface. In vertical heterogeneous media the mechanical properties vary with the depth; the different wavelength propagate in layers of different properties and hence have different propagation velocities. This phenomenon is called geometric dispersion, and the relationship between the phase velocity and the frequency is referred to as dispersion curve. The first step of the test is then the acquisition: surface waves are produced (with active methods) or simply observed (passive methods) at a site, by measuring the particle velocity or acceleration at the free surface in different positions. From these data the phase velocity of different frequencies is estimated with a proper processing, and the apparent dispersion curve of the site, for the given acquisition geometry, is finally obtained. The experimental apparent dispersion curve can be used as objective function for the inversion: the forward model is a 1D model of a layered medium. For each layer, using an elastic or visco-elastic model, 4 mechanical parameters are used (ρ, Η, VS VP): the problem is a linear differential Eigen problem, and has a multi- modal solution